Impatience and uncertainty: experimental decisions predict adolecents' field behavior - Sutter, Matthias; Kocher, Martin; Glätzle-Rützler, Daniela; Trautmann, Stefan T. (Münchener Wirtschaftswissenschaftliche Beiträge, 2010)
We study risk attitudes, ambiguity attitudes, and time preferences of 661 children and adolescents, aged ten to eighteen years, in an incentivized experiment. We relate experimental choices to field behavior. Experimental measures of impatience are found to be significant predictors of health related field behavior and saving decisions. In particular, more impatient children and adolescents are more likely to spend money on alcohol and cigarettes, have a higher body mass index (BMI) and are less likely to save money. Experimental measures for risk and ambiguity attitudes are only weak predictors of field behavior.